MANAJEMEN RANTAI PASOK AGRIBISNIS GOLDEN MELON APOLLO DI KOTA CILEGON - Sulaeni, Sulaeni; Suherman, Suherman (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2022)
The distribution mechanism of the golden melon supply chain in Cilegon City consists of Farmers with Collecting Traders, Collecting Traders with Retailers, Retailers with consumer risks that exist at this level, where traders are fully the responsibility of retailers. the risk faced by traders is the price of the product that goes up and down and when the Golden Melon is damaged and rotten, or is not sold out. The distribution of this Golden Melon supplier is running relatively well, from the farmer level to the product to the final consumer. The collecting traders always prioritize on time delivery and ensure the quantity and quality of Golden Melon, if there is a delay there is usually communication between farmers and traders, so that delays can be tolerated within the previously agreed time period. Information flows of Golden Melon in Cilegon City include Farmers with Collecting Traders, Collecting Traders with Retailers, Retailers with Consumers. The flow of information between retailers and final consumers by Golden Melon in Jombang District is well done. This is indicated by the reciprocal communication between the supply chain actors of Golden Melon, and the trust between merchants and consumers.